Analysis of the training loads of recreational track and field athletes who have participated in mass start competitions during the COVID-19 pandemic - Bonova, I. (Knowledge - International Journal, 2021)
Introduction: The long-term benefits from recreational sports practice have been well researched. Nowadays, the COVID-19 pandemic has brought new, unexpected challenges, which makes it particularly important for professional athletes to be able to consider physical activity and sport from a different perspective and to reorientate their goals in sports accordingly. In professional sport, athletes strive to achieve top results, which requires extreme physical and mental effort, often realized on the border between illness and health. After the end of their racing career, many athletes stop sports practice altogether. Purpose: The present study aimed to explore the transition from a professional competitive career to recreational sports practice as represented by the daily life of ex-runners in middle and long distances. To achieve this goal, the author has analyzed the running loads of runners who have gone past the phase of top and stable sports achievements and have reoriented themselves to the field of sports for recreation. Methodology: For the purpose of this research, Polar Vantage V heart rate monitors were used. Data collected over a 5-month period (October 2020 - February 2021) were analysed - for the group as a whole and for each subject individually. The following parameters of the training loads were examined: total kilometres per month and for 5 months, number of training sessions per month and for 5 months, average heart rate for the best training session of the month, and zones of intensity (Z5-Z1), presented as a percentage distribution of training load time per month and for 5 months. Results: This study included 10 recreational runners (5 men and 5 women), of mean age 36.4 (SD± 4.03), mean weight 63 kg (SD±8.7), mean BMI 20.7 (SD±1.7), mean body fat ratio % 12,7 (SD±4.3). All data were analyzed with the SPSS 26 Statistical program; the statistical significance level was set to p< 0.05. Conclusion: It has been found that recreational runners maintain their lifestyle in the conditions of the COVID-19 pandemic. Recreational runners do not change their habits and perform regularly the planned training session, as reported in this article. They keep taking part in all the planned starts from the chain of mass events (Sofia Marathon, Balkan Marathon Championship - Kyustendil, national championships, cross country, Run - Bulgaria events). Therefore, reorientation to recreational sports may allow famous athletes to stay in sports actively and to maintain good physical and mental health and social well-being.